Disguising Reddit sources and the efficacy of ethical research - Reagle, Joseph (Ethics and information technology, 2022)
Concerned researchers of online forums might implement what Bruckman ( 2002 ) referred to as disguise . Heavy disguise, for example, elides usernames and rewords quoted prose so that sources are difficult to locate via search engines. This can protect users (who might be members of vulnerable populations, including minors) from additional harms (such as harassment or additional identification). But does disguise work? I analyze 22 Reddit research reports: 3 of light disguise, using verbatim quotes, and 19 of heavier disguise, using reworded phrases. I test if their sources can be located via three different search services (i.e., Reddit, Google, and RedditSearch). I also interview 10 of the reports’ authors about their sourcing practices, influences, and experiences. Disguising sources is effective only if done and tested rigorously; I was able to locate all of the verbatim sources (3/3) and many of the reworded sources (11/19). There is a lack of understanding, among users and researchers, about how online messages can be located, especially after deletion. Researchers should conduct similar site-specific investigations and develop practical guidelines and tools for improving the ethical use of online sources.